M7 Should we be paying more attention to nutritional status in non-tuberculous mycobacterial lung disease?. (12th November 2019) - Hussain, N; Kagka, M; Weekes, E; Breen, R; Milburn, H
Abstract : Introduction: The prevalence of non-tuberculous mycobacterial pulmonary disease (NTMPD) disease is growing, however data surrounding nutritional factors and disease activity are sparse. The association between vitamin D levels and tuberculosis is well recognised; this is yet to be replicated in NTMPD. Higher mortality rates are associated with low BMI scores in NTMPD. We aimed to assess nutritional status of patients with NTMPD and to link this with disease activity and outcome. Methods: Patients with NTMPD were identified and recruited in clinics. Baseline and 6-month follow-up assessments included blood tests, CT chest imaging, and nutritional and frailty status. Nutritional status was correlated with disease severity and outcome using correlation analysis and logistic regression. A total of 29 patients have been included in analysis to date. Results: We found significant negative associations between albumin levels and disease activity as measured by ESR and CRP (r2 =-0.441, p=0.045 and r2 =-0.458, p=0.014 respectively). There was a significant negative correlation between vitamin D levels at 6-months and ESR (r2 =- 0.818, p=0.013); vitamin D levels were significant predictors of ESR levels (F (3, 1), p=0.018). Higher BMI scores correlated with lower disease activity on chest imaging (r2 =-0.691, p=0.009). Poor gait scores correlated with higher disease activity on radiology and number of symptoms ((r2 =-0.423, p=0.028). More time taken to complete 5-chair stands was associated with increased disease activity on imaging (r2 =0.474, p=0.012). Gait scores were also significant predictors of ESR (3, 16) p=0.028. A further two patients with very poor levels of nutrition and frailty died before the 6-month follow-up Frailty tests were not significant predictors of outcome as reflected by change in radiology findings after 6 months p<0.05. Conclusions: Lower BMI scores and lower levels of vitamin D and albumin are associated with higher levels of disease activity in NTMPD, reflecting an association between nutritional status and disease activity. Patients who score poorly on frailty tests seem to have higher disease activity. These results suggest that we should be paying more attention to nutritional status in NTMPD. We plan to expand on this data in order to assess whether nutritional factors have a further association with outcome.